2013
DOI: 10.3390/app3020469
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Presence of Nonionic Surfactant Brij35 on the Mobility of Metribuzin in Soil

Abstract: Given the water scarcity becoming endemic to a large portion of the globe, arid region irrigation has resorted to the use of treated, partially treated, or even untreated wastewaters. Such waters contain a number of pollutants, including surfactants. Applied to agricultural lands, these surfactants could affect the fate and transport of other chemicals in the soil, particularly pesticides. A field lysimeter study was undertaken to investigate the effect of nonionic surfactant, Brij35, on the in-soil fate and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…Non-ionic surfactants are even more effective in increasing enzyme stability and positively improving efficacy of enzyme-substrate interactions (Eriksson et al, 2002). Moreover, many surfactants such as alcohol ethoxylates and alkylphenol ethoxylates that are biodegradable in the soil environment are safer as result of their rapid breakdown to less toxic, less persistent and less estrogenic compounds than alkyl polyphenol ethoxylates (ElSayed and Prasher, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Non-ionic surfactants are even more effective in increasing enzyme stability and positively improving efficacy of enzyme-substrate interactions (Eriksson et al, 2002). Moreover, many surfactants such as alcohol ethoxylates and alkylphenol ethoxylates that are biodegradable in the soil environment are safer as result of their rapid breakdown to less toxic, less persistent and less estrogenic compounds than alkyl polyphenol ethoxylates (ElSayed and Prasher, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Triazine herbicides constitute one of the largest groups of pesticides used throughout the world (Salman et al, 2012;Hamza et al, 2015). Triazinones, such as metribuzin (4-amino-6-tert-butyl-4,5-dihydro-3 methyltio-1,2,4-triazin-5-one) are used worldwide to control broadleaf weeds in crops such as potatoes, soybeans and other vegetable crops (El Sayed and Prasher, 2013). As a result of its widespread use, metribuzin paid more attention as it considered a potential environmental contaminant (Mehdizadeh, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Previous study showed that a surfactant increased the mobility of metribuzin in soil [28]. Thus, surfactants can be used to remove residual pesticides in soil by solubilizing sorbed pesticides [29].…”
Section: Effect Of Triton X-100 On Absorption Of Procymidone In Soil By Lettucementioning
confidence: 99%